Ulli beier, Obotunde Ijimere and Theopaneia in the imprisonment of Obatala (2016)
Ulli Beier's attachment to the arts and the peoples of Nigeria is in itself unique. His choices, in association, research and artistic efforts portray this in an unequivocal manner. Obotunde Ijimere, another of Beier's creations, is the author of The Imprisonment of Obatala. This study examines the posture and the context in which Beier perceives the Yoruba, his involvement with the people's theopanic visions and the significance of the experiences to his work in Nigeria.